Cartilage Subsurface Changes to Magnetic Resonance Imaging UTE-T2* 2 Years After Anterior Cruciate Ligament Reconstruction Correlate With Walking Mechanics Associated With Knee Osteoarthritis. Issue 3 (March 2018) - Titchenal, Matthew R.; Williams, Ashley A.; Chehab, Eric F.; Asay, Jessica L.; Dragoo, Jason L.; Gold, Garry E.; McAdams, Timothy R.; Andriacchi, Thomas P.; Chu, Constance R.
Background: Anterior cruciate ligament (ACL) injury increases risk for posttraumatic knee osteoarthritis (OA). Quantitative ultrashort echo time enhanced T2* (UTE-T2*) mapping shows promise for early detection of potentially reversible subsurface cartilage abnormalities after ACL reconstruction (ACLR) but needs further validation against established clinical metrics of OA risk such as knee adduction moment (KAM) and mechanical alignment. Hypothesis: Elevated UTE-T2* values in medial knee cartilage 2 years after ACLR correlate with varus alignment and higher KAM during walking. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Twenty patients (mean age, 33.1 ± 10.5 years; 11 female) 2 years after ACLR underwent 3.0-T knee magnetic resonance imaging (MRI), radiography, and gait analysis, after which mechanical alignment was measured, KAM during walking was calculated, and UTE-T2* maps were generated. The mechanical axis and the first and second peaks of KAM (KAM1 and KAM2, respectively) were tested using linear regressions for correlations with deep UTE-T2* values in the central and posterior medial femoral condyle (cMFC and pMFC, respectively) and central medial tibial plateau (cMTP). UTE-T2* values from ACL-reconstructed patients were additionally compared with those of 14 uninjured participants (mean age, 30.9 ± 8.9 years; 6 female) using Mann-Whitney U and standard t tests. Results: Central weightbearing medial compartment cartilage of ACL-reconstructed knees was intact on morphological MRI. Mean UTE-T2* values were elevated in both the cMFC and pMFC of ACL-reconstructed knees compared with those of uninjured knees ( P = .003 and P = .012, respectively). In ACL-reconstructed knees, UTE-T2* values of cMFC cartilage positively correlated with increasing varus alignment ( R = 0.568). Higher UTE-T2* values in cMFC and cMTP cartilage of ACL-reconstructed knees also correlated with greater KAM1 ( R = 0.452 and R = 0.463, respectively) and KAM2 ( R = 0.465 and R = 0.764, respectively) and with KAM2 in pMFC cartilage ( R = 0.602). Conclusion: Elevated deep UTE-T2* values of medial knee cartilage 2 years after ACLR correlate with 2 clinical markers of increased risk of medial knee OA. These results support the clinical utility of MRI UTE-T2* for early diagnosis of subsurface cartilage abnormalities. Longitudinal follow-up of larger cohorts is needed to determine the predictive and staging potential of UTE-T2* for posttraumatic OA.